Neuropsychological diagnosis in the acute period of ischemic stroke - A M Tynterova; S A Perepelitsa; Yu E Skalin; I V Reverchuk; O A Tikhonova; A A Grishina AA (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The aim of the study — to establish the severity of cognitive, psychoemotional, motivational and behavioral disorders in patients after acute period of ischemic stroke.Materials and methods. The study included 60 patients with a diagnosis of ischemic stroke. Depending on severity of neurological deficit according to the national stroke scale (NIHSS), patients were divided into two groups: group 1 — 30 patients with an NIHSS score of 0 to 8, associated with mild neurological deficit, group 2 — 30 patients with an NIHSS score of 9 to 15, associated with moderate neurological deficits. The study was conducted on the 7th day of treatment and included: assessment of the cognitive status according to the Montreal Cognitive Assessment scale; assessment of the level of distress, depression, anxiety and somatization using the Four Dimensional Symptom Questionnaire; assessment of mental and physical asthenia according to the MFI-20 scale, level of self-control using the Rotter’s Locus of Control Scale and assessment of the personality and the familial unconscious in Szondi’s test. Results. The study established the prevalence of depression and cognitive impairment in patients with moderate neurological deficits. Patients with mild neurological deficits are characterized by a moderate level of somatization, mental and physical asthenia, a low level of self-control in relation to health, low adherence to treatment and poor motivation to recover.Conclusion. The results of the study indicate the need inclusion of assessment of psychoemotional factors and personal resources of the patient in relation to illness and recovery in early diagnosis of patients with stroke. Along with neurological deficits, it is necessary to assess the cognitive, emotional and motivational levels of the “internal picture of the disease”. This can help determine the patient’s basic compensatory and adaptive capabilities and develop individual rehabilitation strategies.